Radiographic evaluation of the healing process of alveolar abscess through regulation of VEGF and angiogenesis - Asykarie, Ichda Nabiela Amiria; Epsilawati, Lusi (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2024)
Objectives: This review article aims to explain how the regulation of vascular endothelial growth factor (VEGF) and angiogenesis on alveolar abscess healing process evaluation using radiograph. Review: The databases used in this review are Google Scholar, PubMed, and Science Direct. A total of 1280 search results appeared based on keywords. The search results were selected by title and abstract according to their relevance to the review topic. A total of 24 literatures were reviewed. The alveolar bone destruction is one of the signs of an inflammatory lesion in the alveolar bone. Bone damage that occurs in cases of the abscess will reduce the absorption of x-rays thereby giving a radiolucent appearance on radiographic examination. A radiographic examination is a supporting examination that can be used to develop the healing process. The processes of angiogenesis and osteogenesis of bone homeostasis will complement each other for the bone healing process, while VEGF is a growth factor that can increase the expression of BMPs and osteoblast differentiation so that the bone healing process can take place properly. Conclusion: VEGF plays a significant role in both bone healing and regulation of vascular development and angiogenesis. However, excessive VEGF can also be harmful to the process of bone repair because it can stimulate the recruitment of osteoclasts. Therefore, VEGF regulation has an important role in apical abscess healing, and radiographic images that are quantitatively analyzed can be used to quantify this healing process.